Au13−nAgn clusters: a remarkably simple trend. Issue 45 (29th October 2015) - Munoz, Francisco; Varas, Alejandro; Rogan, José; Valdivia, Juan Alejandro; Kiwi, Miguel
Abstract : The planar to three dimensional transition of Au13− n Ag n clusters is investigated. Abstract : The planar to three dimensional transition of Au13− n Ag n clusters is investigated. To do so the low lying energy configurations for all possible concentrations ( n values) are evaluated. Many thousands of possible conformations are examined. They are generated using the procedure developed by Rogan et al. in combination with the semi-empirical Gupta potential. A large fraction of these (the low lying energy ones) are minimized by means of Density Functional Theory (DFT) calculations. We employ the Tao, Perdew, Staroverov, and Scuseria (TPSS) meta-GGA functional and the Perdew, Burke and Ernzerhof (PBE) GGA functional, and compare their results. The effect of spin–orbit coupling is studied as well as the s–d hybridization. As usual in this context the results are functional-dependent. However, both functionals lead to agreement as far as trends are concerned, yielding just two relevant motifs, but their results differ quantitatively.